YouTube dan Pembelajaran Bahasa: Bagaimana Persepsi Siswa dalam Implikasinya? - Jakob, Fidela Evania; Jakob, Juvrianto Chrissunday (P3M POLITEKNIK NEGERI AMBON, 2023)
In today's educational landscape, digital learning has emerged as a new learning model. Students prefer videos on YouTube and other technology-enabled language learning platforms. YouTube, as one of the most prominent social media platforms in today's globe, also has an impact on education. Technology that is integrated into students' life can give valuable input, particularly in enabling and strengthening English language knowledge and skills. This article presents qualitative study on students' perspectives of how learning English through YouTube is good and helps them learn English. This study included students from SMP 4 Parepare who utilized YouTube as an English learning medium, and data was gathered through interviews using a case study design. The findings of this study revealed that all students have numerous advantages in improving their English language skills, and that it is easily accessible on practically every student's device and can be utilized in any setting to assist and motivate them to learn English. Students only have troubles if their internet connection is poor. All pupils expressed satisfaction with the use of the YouTube application to learn English.Keywords: language learning, students’ perception, gadget, social media